Creation Of Multilingual Teaching Materials Focused On Content And Background Of Ngada Culture For Primary 1st Grade - et. al., Yosefina Uge Lawe, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research was conducted in line with the development of existing technology. The teaching materials are developed using the ADDIE model, which consists of five steps, namely: 1) analyze, 2) design, 3) development, 4) implementation, 5) evaluation. In this study, sources of data were obtained from teachers as material / content experts, lecturers as language experts, and design experts. Components assessed by material experts are content feasibility, linguists on the appropriateness of language use, design experts on product design appropriateness. The suitability of the developed teaching materials in terms of the results of the assessment or validation of content or material experts obtained a score of 79 with an average of 4.4, and local language experts received a score of 44 with an average of 3.6, Indonesian language experts got a score of 43 with an average of 4.7. Product design experts obtained a score of 43 with an average of 3.9. Thus, multilingual teaching materials based on content and the local cultural context of the Ngada ethnic group on Theme 6 Clean, Healthy, and Beautiful Environment can be used.